‘QUEENMOTHER’ CONCEPT IN THE UPPER WEST REGION OF GHANA: IS THIS ADVANCEMENT OR AN EMERGING CONFLICT WITH TRADITION IN A PATRIARCHAL SOCIETY? - Kilian Nasung Atuoye; Felicia Safoa Odame (European Scientific Journal, ESJ, 2013)
The concept of ‘queenmother’ is not new in Africa. Scholars have indicated the importance of this institution in Ghanaian traditional political system. With increasing women’s empowerment, there is a growing realization that women are co-agents of nation building resulting in the expansion of roles of queen mothers as conduits of development. Consequently, patriarchal societies without queen mothers such as the Upper West Region (UWR) of Ghana are encouraged to install one. While this practice has been going on for centuries in matriarchate, its replication in patriarchates raises questions and concerns. Using interpretative methods involving focus group discussions and in-depth interviews with traditional leaders and elders, this research explored the perceptions and challenges of this emerging concept in the UWR. The concept as practiced in matriarchate has been adopted wholesale into patriarchates and this may have led to the perceived nonfunctional nature of the concept. This concept also conflicts with the traditional and deep-seated cultural values of the people, especially those related to the marriage institution. Furthermore, the perceived roles of queen mothers seem to conflict with those already performed by traditionally recognized ‘Tindaamba’ and ‘pognaaba’. To avoid potential conflicts already existing women leaders (pognaaba) should play the role of ‘queenmothers’ in these societies.